New method of monitoring the transmission range of coal seam water injection and correcting the monitoring results. (June 2021) - Chen, Jian; Cheng, Weimin; Wang, Gang; Li, Haomiao; Li, Yanyan
Highlights: A new method of monitoring the transmission range of coal water injection is designed. The first appearance of P-wave after water injection is a sign of data screening. The reconstructed fracture by CT scan is used to correct the envelope result. Abstract: This study proposes a new experimental method of monitoring the transmission range of coal seam water injection on the basis of acoustic emission array monitoring technology. Through theoretical analysis and experimental verification, data on the characteristic signs that can confirm the water transmission to the monitoring path were found. In accordance with these data, the water transmission contour was enveloped. Subsequently, the water transmission's calculated distance, and fracture space parameters which were reconstructed by computed tomography (CT) scanning, were used to modify the control points of the water transmission contour. Results were compared with experimental slices to confirm the feasibility and correctness of the proposed monitoring technology. Furthermore, the threshold range of the wave parameter change when the water touches the monitoring path was determined in accordance with the range of the wave parameter change monitored in the effective monitoring path.